1991
DOI: 10.1159/000138790
|View full text |Cite
|
Sign up to set email alerts
|

Binding of [<sup>3</sup>H]-Dopamine to Human Lymphocytes: Possible Relationship to Neurotransmitter Uptake Sites

Abstract: Freshly isolated human lymphocytes from 11 healthy subjects had specific binding sites for dopamine which were dependent on time, temperature and sodium, and appeared to follow Michaelis-Menten kinetics. The apparent affinity constant (KD) of human lymphocytes for dopamine and the maximal number of binding sites (Bmax) were 109 ± 21 nM and 2.66 ± 1.75 pmol/107 cells, respectively. Dopamine binding was markedly affected by cocaine (IC50 = 150 nM) and other inhibitors of biogenic amine upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…This effect was associated with the GR-cortisol complex, which regulates transcriptional responses upon binding to a hormone response element, located in the promoter region of the target genes (Reichel & Jacob, 1993). The gene encoding the human serotonin transporter was shown to be identical in neurons and lymphocytes (Faraj et al, 1994(Faraj et al, , 1997, and various studies indicate that the analogy in the uptake of neurotransmitters between both types of cells is actually valid (Faraj et al, 1991(Faraj et al, , 1994(Faraj et al, , 1997Grodzicki et al, 1990;Halbach & Henning, 1989). In addition, we also reported that PBLs from rabbits previously treated in vivo with cortisol presented an effect similar to that observed in human PBLs upon incubation with cortisol in vitro.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This effect was associated with the GR-cortisol complex, which regulates transcriptional responses upon binding to a hormone response element, located in the promoter region of the target genes (Reichel & Jacob, 1993). The gene encoding the human serotonin transporter was shown to be identical in neurons and lymphocytes (Faraj et al, 1994(Faraj et al, , 1997, and various studies indicate that the analogy in the uptake of neurotransmitters between both types of cells is actually valid (Faraj et al, 1991(Faraj et al, , 1994(Faraj et al, , 1997Grodzicki et al, 1990;Halbach & Henning, 1989). In addition, we also reported that PBLs from rabbits previously treated in vivo with cortisol presented an effect similar to that observed in human PBLs upon incubation with cortisol in vitro.…”
Section: Discussionsupporting
confidence: 63%
“…Uptake of serotonin (5-HT) was assayed with tritiated 5-HT ([ 3 H]-5-HT, NEN) essentially as reported in Faraj et al (1991Faraj et al ( , 1994. Cortisol-treated and control samples were incubated for 15 min at 37º C in the presence of 10 -6 M 5-HT (Sigma), doped with [ 3 H]-5-HT in 1.5-ml microtubes (Eppendorf ).…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacological profile overlapped with that obtained by our group in brain and platelet membranes (Rotondo et al 1996): in fact, the different compounds showed the same rank of potency in all these tissues. The lack of activity of mazindol and nomifensine at the level of [ 3 H]PAR binding shows that we were not labeling the dopamine transporter, which is present at a high concentration in lymphocytes (Faraj et al 1991). The presence of the 5-HT transporter in human lymphocytes suggests its possible role in some immune functions, mediated by these cells and by 5-HT, whose role as an immunomodulator is currently emerging (Fillion et al 1996).…”
Section: Discussionmentioning
confidence: 89%
“…Human lymphocytes also have been shown to express some of these reuptake transporters. Dopaminespecific binding sites, as well as a dopamine-selective reuptake system, have been demonstrated on human lymphocyte membranes (35,36). Selective blockade of these monoamine transporters suppressed both the dopamine binding to the specific sites and the uptake of [ 3 H]-dopamine.…”
mentioning
confidence: 99%